Evaluation of the Antioxidant Capacities of Antarctic Macroalgae and Their Use for Nanoparticles Production - N. González-Ballesteros; M. C. Rodríguez-Argüelles; M. Lastra-Valdor (Molecules, 2021)
Macroalgae are sources of bioactive compounds that are interesting from both a chemical and a medical point of view. Although their use in biomedicine has increased significantly in recent years, tests conducted to date have been mostly related to species from temperate latitudes, with the potential application of Antarctic biodiversity being minor. The wide variety of algae species present on Antarctic coastal areas can be a source of new antioxidants. Bearing this in mind, the brown macroalgae Desmarestia antarctica (DA) and the red Iridaea cordata (IC) were selected for the preparation of aqueous extracts with the aim of analyzing their antioxidant activity. This analysis was performed by determining reducing power, total phenolic content, and 2,2-diphenyl-1-picrylhydrazyl free radical scavenging activity. Furthermore, both extracts were employed to synthesize gold and silver nanoparticles. The nanomaterials were fully characterized by means of UV-Visible spectroscopy, transmission electron microscopy, Z potential measurements, and Fourier transform infrared spectroscopy, which confirmed the formation of stable, spherical nanoparticles with mean diameters of 13.7 ± 3.1 and 17.5 ± 3.7 nm for Ag@DA and Ag@IC and 12.6 ± 1.9 and 12.3 ± 1.6 nm for Au@DA and Au@IC. Antioxidant assays were performed after the synthesis of the nanomaterials to evaluate their possible synergistic effect with the extracts. The results suggest that polysaccharides and proteins may play a key role in the process of reduction and stabilization. Finally, for the sake of comparison, the results obtained for the Antarctic macroalgae Desmarestia menziesii and Palmaria decipiens have also been considered in the present work.